What Black Health Means for Bioethics in Canada - Pahwa, Manisha (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Keisha Ray’s Black Health is a poignant examination of the social, political, and cultural determinants of Black people’s health and well-being in the United States. This review reflects on the potential implications of Black Health for health equity and what bioethics could be and do for everyone in Canada.